Synthesis of a [18F]F Estradiol Derivative via Click Chemistry Using an Automated Synthesis Module: In Vitro Evaluation as Potential Radiopharmaceutical for Breast Cancer Imaging - María Emilia Tejería; María Pía Pereira; Juan Pablo Gambini; Pablo Duarte; Javier Gabriel Giglio; Ana María Rey (MDPI AG, 2024)
"Click reactions" are a very useful tool for the selective conjugation of different molecular subunits to produce complex structures in a simple way. In this paper, we present the application of Cu(I)-catalyzed biorthogonal reactions between alkynes and azides to the indirect radiofluorination of an estradiol derivative with potential applications in estrogen receptor imaging. The procedure was fully developed on an automated synthesis platform, and conditions were optimized to achieve the desired product with a reasonable yield without precipitation. Although the biological results were not adequate for a potential radiopharmaceutical, the outcome of this work is valuable since the use of automated platforms is required for the reliable and reproducible preparation of PET radiopharmaceuticals in GMP conditions while limiting the radiation dose rates to the personnel.